Pensamento cenológico na obra de Lina Bo Bardi (1976-1992) - Silva, Mateus Bertone da (2023)
This thesis analyzes theoretically and historically the presence of the theatrical dimension that emerges from the architectural work of Lina Bo Bardi (1914-1992), especially in its mature phase, understood between 1976, when he wrote the article Planejamento ambiental: ‘desenho’ no impasse and goes back to designing for the city of São Paulo, and 1992, the year of his death, through various sources, among them the process records of architectural and urban projects, executed or not, which present emblematic and instigating similarities to the creative processes, as well as to the perceptive and communicative aspects of the space in the Theater. Interlocution with theater groups with which the architect worked over at least three decades, and it’s clear insertion as a constitutive and critical agent of the particular historical contexts in which this production is inserted, were engendered by an original thought, in which the plot between the languages of Architecture and Theater is placed at the service of a “program” at the same time aesthetic and political and from which Lina Bo Bardi’s design epistemology is detached, in a broad sense. In addition to the continuous references made by the architect to concepts of the theatrical universe or even directly to playwrights, it is in the graphicvisual records of the projects that we can observe and decipher, motabilem, that pointed plot and from which a latent and fabled memory of the artifacts, solutions, landscapes and experiences of popular “inspiration” intervene as a guiding narrative: a dramaturgy that takes place incorporated into the very materiality of its primordial artistic language, architecture, through the competence that this art has, like in the theater, to fictionalize. The dialogical reinvention of forms, materials and techniques of “popular” expression, emulating the meanings of this space-time experience through the path of theatricality, is shown as a critical and operative design trick – that is, at the same time of resistance and 'revenge' – through which prefigurations of another possible Modernity are programmed, in a period inflamed by memories and the urgency of action, under the historical climate of uncertainties, but also of hopes, felt with the political reopening and the establishment of the New Republic in Brazil.